2009
DOI: 10.2474/trol.4.78
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear Properties of Rice Husk Ceramics under Dry and Water Lubricated Conditions

Abstract: The authors have developed the new hard porous carbon material "Rice Husk ceramics" (RH ceramics) by carbonizing the mixture of rice husk and phenol resin at 900 °C in inert gas environment. The RH ceramics are composed of amorphous carbon and amorphous silica, about 90 and 10 wt.%, respectively. The friction and wear properties of RH ceramics sliding against austenitic stainless steel (JIS SUS304) were evaluated under dry and water lubricated conditions using a ball-on-disk apparatus. The test results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The improvement in wear and friction under wet sliding compared to dry is summarized in Table 10.10. One of the four reviewed work contradicted this [102]. In this work, it was reported that in dry contact, the h) There were three papers reviewed in which abrasive testing was conducted [50,101,109].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The improvement in wear and friction under wet sliding compared to dry is summarized in Table 10.10. One of the four reviewed work contradicted this [102]. In this work, it was reported that in dry contact, the h) There were three papers reviewed in which abrasive testing was conducted [50,101,109].…”
Section: Discussionmentioning
confidence: 96%
“…Rice husks can also be carbonized through mixing with phenolic resin in an inert gas environment, forming Rice Husk ceramics, or 'RH ceramics'. In 2009, Tuvshin and associates investigated the friction and wear properties of RH ceramics under dry and wet contact conditions [102]. A BOD machine was used, under various loads (0.98 -9.8 N) and sliding velocities (0.02 -1 m/s).…”
Section: K) Rice Husk Fibrementioning
confidence: 99%
“…,米糠 (7)(8)(9)(10)(11)(12) ,籾殻 (13)(14)(15)(16)(17)(18) などを原料とした植物 由来炭素材料の研究が進められている。炭素材料は自己潤滑 性,耐薬品性,耐熱性に優れており,金属材料を使用できない 薬液中や,潤滑剤を使用できない高温乾燥の環境下での摺動材 料として用いられる。堀切川らは,フェノール樹脂をバインダ に使用して,米糠と籾殻に由来する RB セラミックスと RH セ ラミックスを製造した。900-1000℃で焼成した RB セラミッ クスとRH セラミックスは,摩擦係数0.07-0.17,比摩耗量1.0×…”
Section: はじめにunclassified